1998
DOI: 10.1159/000014017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyunsaturated Fatty Acids

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFA) are essential for normal development. Fetal accretion of LC-PUFA occurs during the last trimester of gestation; therefore, premature infants are born with minimal LC-PUFA reserves. Recent studies indicate that the newborn can synthesize LC-PUFA from essential fatty acid precursors; however, the extent of de novo synthesis remains to be established. Postnatally, human milk provides LC-PUFA to the newborn. Maternal LC-PUFA reserves depend upon diet and can be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 79 publications
4
53
1
2
Order By: Relevance
“…Whether nutrition or reduced brain DHA and AA is part of the pathology behind the delays in brain development and function has not been reported. It is notable that the transitional milk from the sows was similar to that reported for women consuming Western diets [40]. The omnivorous diet of humans supports greater amounts of DHA in maternal milk [25,40] and may prove advantageous to infant DHA status during Dex treatment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Whether nutrition or reduced brain DHA and AA is part of the pathology behind the delays in brain development and function has not been reported. It is notable that the transitional milk from the sows was similar to that reported for women consuming Western diets [40]. The omnivorous diet of humans supports greater amounts of DHA in maternal milk [25,40] and may prove advantageous to infant DHA status during Dex treatment.…”
Section: Discussionsupporting
confidence: 56%
“…It is notable that the transitional milk from the sows was similar to that reported for women consuming Western diets [40]. The omnivorous diet of humans supports greater amounts of DHA in maternal milk [25,40] and may prove advantageous to infant DHA status during Dex treatment. Nevertheless, LC PUFA status is likely vulnerable to the effects of Dex in the very premature infant with minimal fat stores and fed milk formula without AA or DHA or intravenous lipid.…”
Section: Discussionsupporting
confidence: 56%
“…4,20). However, animal studies have shown that when n-3 fat sources are inadequate during early neural development, then the levels of brain and retinal DHA decline (4,(20)(21)(22)(23)(24). This has also been confirmed in autopsy studies of human infants that were fed a vegetable oil-based formula with low n-3 fat sources vs. breast-feeding in which preformed DHA was present (25)(26)(27).…”
Section: Dha Compositionmentioning
confidence: 88%
“…AA is also the principal n-6 fatty acid in the brain; together with n-3 PUFAs, it plays an important role in the development of the infant brain (Hamosh and Salem, 1998). A strong relationship has been reported between the AA level in plasma and firstyear growth in preterm infants (Carlson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%